Sulfation of Glycosaminoglycan Hydrogels Instructs Cell Fate and Chondral versus Endochondral Lineage Decision of Skeletal Stem Cells In Vivo. (6th November 2021) - Chasan, Safak; Hesse, Eliane; Atallah, Passant; Gerstner, Matthias; Diederichs, Solvig; Schenker, Astrid; Grobe, Kay; Werner, Carsten; Richter, Wiltrud
Abstract: Exit from multipotency and lineage commitment of mesenchymal stroma cells (MSC) depends on microenvironmental cues from the stem‐cell niche but steering cell fate into the desired lineage in vivo remains a challenge. Increasing evidence suggests that glycosaminoglycans (GAGs) can be used to activate or sequester growth factors with the specific action depending on sulfation levels. It is postulated that differentially sulfated biomaterials can aid developmental lineage instruction of MSC to guide tissue morphogenesis in vivo. By application of a new injectable TGFβ‐loaded heparin‐PEG‐hydrogel the authors here gain the ability to control skeletal stem‐cell fate in vivo down the chondral versus the endochondral pathway depending on the sulfation status. High sulfation allows for long‐term TGFβ‐retention and silencing of Hedgehog‐, BMP‐, and WNT‐pathways installing prochondrogenic and antihypertrophic cues which permitted in vivo growth of permanent, collagen‐type‐II‐rich neocartilage with long‐term resistance to calcification and bone formation. Selective 6‐ O / N ‐desulfation of heparin supports Hedgehog/BMP/WNT‐signaling switching lineage commitment into endochondral differentiation with strong hypertrophic/osteogenic marker expression and tissue calcification. This work identifies GAG sulfation as a crucial niche instruction signal to determine the chondral stem‐cell fate via silencing of prohypertrophic pathways, providing the first proof‐of‐principle on how GAG modification‐patterns can determine cell lineage‐choice during tissue morphogenesis in vivo. Abstract : Steering mesenchymal stem‐cell fate into a desired lineage in vivo remains thus far unsolved. Niche instruction features are discovered that determine cell fate between two different lineages, the chondral versus endochondral pathway in vivo. Glycosaminoglycan‐sulfation‐dependent tuning of the activity of several growth‐factor pathways allows for the first time to grow stable nonmineralizing cartilage from skeletal stem‐cells for regeneration therapy.